Risk Factors of Bacterial Contamination on Healthcare Workers’ Smartphone - Kurniawan, Muhammad; Aditami, Fakikha (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Smartphone is a rapidly growing communication and information technology. Smartphone has many advantages for healthcare workers in terms of communication and information access. Smartphones that are contaminated by bacteria carry significant risk for patients in hospital. Smartphone users’ behavior is considered a factor that predisposes contamination of bacteria on the smartphones. The reasearch need to be done to investigate factors affecting bacterial contamination on healthcare workers’ smartphones. This was an observational analytic study conducted using cross-sectional design. This study was conducted at PKU Muhammadiyah Gamping Hospital on April until June 2018. Study participants included 94 healthcare workers at PKU Muhammadiyah Gamping Hospital who met inclusion criteria, namely those who had and brought their smartphones. Each participant was asked to fill a questionnaire. Each smartphone was swabbed to obtain sample for culture with TSA medium, subsequently incubated at 37oC for 24 hours followed by gram staining. Data analysis was conducted using Chi Square or Fisher test. The results showed that 86.2% of healthcare workers used smartphone more than three times during work hours at hospital, 85.1% did not use smartphone during physical examination or therapeutic intervention, 73.4% did not clean their smartphone everyday, and 87.2% smartphone were contaminated by bacteria showing the morphology of gram negative bacilli and gram positive cocci. There was no significant influence of frequency of smartphone use at hospital (p=1.000), using smartphone during physical examination or therapeutic intervention (p=0.686), and cleaning smartphone everyday (p=1.000) on bacterial contamination on healthcare workers’ smartphones. In conclusion, 87.2% of healthcare workers’ smartphones were contaminated by bacteria. Frequency of smartphone use at hospital, smartphone use during physical examination or therapeutic intervention, and cleaning smartphone everyday did not affect bacterial contamination over healthcare workers’ smartphones.